(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
INHA International University (IIU) is a renowned higher education institution with a rich history spanning several decades. Originally established as a specialized university focused on maritime education, IIU has evolved into a comprehensive university offering a wide range of academic programs. INHA International University is a beacon of academic excellence and cultural diversity located in the heart of Incheon, South Korea. With a rich history spanning several decades, the institution has grown from humble beginnings to a world-renowned center of higher learning that fosters collaboration and innovation.